Awareness and Need for Knowledge of Health and Safety among Dairy Farmers Interviewed in Uganda - Lunner-Kolstrup, Christina; Ssali, Tonny Kiggundu (Frontiers in Public Health, 2016)
Introduction Safe working conditions are essential for healthy living and for ensuring food security among farmers and farm communities in developing countries. There is limited research on this topic, and documentation is essential to understand and change patterns of human health and safety. Methods In May 2014, six male and female farmers on four dairy farms in Uganda and a female veterinarian were interviewed about their awareness and attitudes to agricultural risk factors, health, and safety. In addition, transect walks were conducted on the four dairy farms. Results The dairy farmers reported health and safety concerns, e.g., diarrhea, coughs, fever, cuts while using machetes in plantations, bruises when handling animals, and dizziness and poisoning symptoms from using different agrochemicals, and considered these an occupational hazard. The most important topic mentioned was the use of agrochemicals and drugs on livestock. The farmers spray their animals with insecticides to prevent ticks, lice, tsetse flies, and other biting nuisance flies, using a backpack or hand sprayer. Spraying is conducted without personal protection equipment, which is considered too expensive and difficult to obtain. The farmers reported that they usually feel dizzy, vomit, and have pain and a burning feeling in their face and eyes after spraying. The symptoms are sometimes so severe that they require treatment. In such cases, the farmers buy medication without a prescription at the local drugstore, where the storekeeper often has limited or no knowledge of agrochemicals or drugs except for dosage. Agricultural health and safety training in the region is non-existent, and the farmers expressed a need and desire for improvements in this area. Conclusion The level of knowledge and awareness of agricultural health and safety risks, disease, and injury prevention among the Ugandan dairy farmers interviewed was low. The farmers mentioned few agriculture-related complaints, injuries, or diseases except poisoning from using agrochemicals. Training on health and safety in Ugandan agriculture is urgently needed.